And then there was one : investigating ARIS, the Victorian Adult Education and Resource Information Service - Hazell, Pat (Adult Literacy and Numeracy Australian Research Consortium., 2002)
The first of the four questions that the national ALNARC workplan for 2001-2002 sought to address was: What does the past tell us about adult literacy and numeracy policy, provision and research? This project provides one small answer to that question, by examining the Victorian Adult Education and Resource Information Service (ARIS), which has operated as a professional support organisation to the field of adult literacy and numeracy for more than ten years. The field of adult literacy and numeracy provision in Australia has developed and grown over the past 20 years. From a focus on student-centred learning and meeting the needs of the community, it has evolved into a multi-faceted field incorporating community, TAFE institutional and workplace provision. Through the ebbs and flows of politics and pedagogies, sites of delivery and changing practitioner perspectives, the field has needed and provided for itself, mechanisms for support. There are two mechanisms in particular that have developed: professional associations and information services. The purpose of this research was to examine ARIS as an organisation providing a support service to the literacy and numeracy field; to consider factors that influence its role, effectiveness and sustainability, in order to look ahead and consider how the ARIS experience may offer insights into ways that the support needs of the literacy and numeracy field might be met in the future.